ANALYSIS OF THE IMPACT OF UMRAH TRAVEL SUSPENSION DUE TO COVID-19 ON HAJJ AND UMRAH TRAVEL AGENTS - Hasrun Afandi UmpuSinga; Agus Alimuddin (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
The Covid-19 extensive has brought almost severals collisions that chalk up occurred in indefinite countries, including the country that is a religious tourism destination for Muslims in the world, namely Saudi Arabia, all the more the Covid-19 widespread press for the sovereign state of Saudi Arabia to constitute procedures to understate the spread out diffuse of Covid-19 in its sovereign state, namely by make a policy of suspension of Umrah travel. The issuance of the suspension policy resulted in the cancellation of all Umrah trips from all countries to these destination countries, of course, it would have an impact on companies that run businesses in the field of travel. This discover focus to conclude the impression of the suspension of Umrah expedition outstanding to Covid-19 on the patronage of hadj and umrah globetrot agents, the contemplate was conducted at PT Saudi Patria Wisata situated in underground City, Lampung Province. collections solicitation approaches were carried elsewhere nailed down influential collections and less important data, videlicet press conference environment notes, examinations and documentation, collections psychoanalysis approaches were carried elsewhere by elaborating the examination conclusions victimisationing causative methods. The determination of this contemplate discloses that the Covid-19 widespread has an consequence on the continuance of the corporation and furthermore the consequence on employees.